Patterns of Symmetry Expression in Angiosperms: Developmental and Evolutionary Lability - Naghiloo, Somayeh (Frontiers in Ecology and Evolution, 2020)
Variation in flower symmetry is a remarkable aspect of flowering plant diversity. Multiple evolutionary transitions from an ancestral form of radial symmetry to bilateral symmetry and reversals from bilateral to radial symmetry have occurred during angiosperm evolution. The high incident of symmetry transitions poses the question concerning the homology of underlying developmental processes. I conducted a comprehensive study of developmental expression of symmetry across angiosperms covering 72 families and 39 orders. A wide range of timing for the expression of symmetry was found from organ initiation, to enlargement, to late differentiation of organs. In many studied genera, the symmetry pattern was transient during development. Mapping the floral symmetry patterns on the phylogenetic tree indicated the scattered distribution of patterns across angiosperms. The expression of symmetry was also versatile within families. The developmental constraints exerted by the inflorescence, bracts, neighbor flowers or neighbor organs within a flower could provide a possible explanation for the observed variation of symmetry expression.